(untitled) (International Seven Journal of Multidisciplinary, 2024)
Cinematic tourism is an expanding phenomenon that examines the interaction between audiovisual products and tourist behavior, and their impact on destinations. This field investigates how films and TV shows shape perceptions of destinations and attract visitors, creating new tourism flows and economic opportunities. Actor-Network Theory (ANT) provides a nuanced approach to this study by considering the complex networks of human and non-human actors involved. Developed by Bruno Latour, Michel Callon, and John Law, ANT highlights the significance of these networks in shaping social and economic phenomena. Applying ANT to cinematic tourism reveals how films, tourists, destinations, and local actors are interconnected. This theoretical perspective involves using various research methods, including interviews, discourse analysis, and field observations, to understand how audiovisual representations influence tourist attraction and how destinations respond. ANT helps identify gaps and opportunities in the tourism sector, such as the underutilization of the audiovisual sector by many destinations. Van der Duim, Ren, and Jóhannesson (2013) emphasize ANT’s focus on multiplicity and ontological politics, arguing that tourism is composed of multiple realities and organizing attempts. They suggest that ANT provides a richer understanding of tourism dynamics by analyzing diverse interactions. Paget, Dimanche, and Mounet (2010) demonstrate how new associations between human and non-human actors, facilitated by a "leader translator," can drive a company’s success within a tourist destination by reconfiguring resources into innovative products. Chen and Wu (2013) further illustrate this by using ANT and social affordance to analyze how postmodern attractions, like those themed around Jimmy, are constructed through relational networks. This approach offers a dynamic perspective on tourism attractions, revealing how various actors shape their development.